Subitizing in Tactile Perception - Riggs, Kevin J.; Ferrand, Ludovic; Lancelin, Denis; Fryziel, Laurent; Dumur, Gérard; Simpson, Andrew (Psychological science, 2006)
Enumerating small sets of up to 3 to 4 items is fast, accurate and effortless and is known as subitizing (Kaufman, Lord, Reese & Volkmann, 1949) but gets slower, less accurate and more effortful with more than 4 items (counting). For over a hundred years (Jevons, 1871; Warren, 1897) researchers have focused on visual enumeration and many theories propose that subitizing and counting are two distinct processes in visual perception (Mandler & Shebo,1982; Trick, & Pylyshyn,1994; Dehaene & Cohen,1994). Here we demonstrate for the first time that subitizing also occurs in tactile perception.In a standard visual subitizing task, subjects are asked to name the number of items presented on a computer screen as accurately and as fast as possible. Typical findings are that accuracy is near perfect for small set sizes up to 3 items, but starts to fall off at 4 items. Naming times exhibit a marked discontinuity producing a shallow slope for 1 to 3 items (40 to 100 ms/item in adults) and a much steeper slope from 4 items upwards (250 to 350 ms/item). In children these naming times are considerably greater (200 ms/item for small set sizes and 1000 ms/item at larger set sizes). It is important to note that subitizing is characterized by a discontinuity in the naming time slopes and not by the absolute values of the slopes themselves (Trick, & Pylyshyn, 1994). Thus children produce the subitizing / counting discontinuity in much the same way as adults do (Svenson & Sjöberg, 1978).To investigate subitizing in tactile perception, we designed software and built novel apparatus to simultaneously stimulate the fingertips of both hands. Each hand rested naturally on a separate box with the fingertips spaced well apart from each other. Participants were asked to name the number of stimulated fingertips as quickly and as accurately as possible.